(untitled)
In the Macedonian language territory there are many names for birds of the order of Strigiformes (bu, buf, buv, buh, buval, buhal, b’uhƒl, b’uh‚l, buhel, buarec, buo, b’uho, b’uhalo, bulut, bul’utin, b’ula ; ut, utka, ’utalen; lul’ejka, ulejka; d’umo;